GELIAT INDUSTRI SASTRA DI SEKOLAH: PEMBELAJARAN SASTRA BERBASIS INDUSTRI KREATIF - Rohmah, Muttafaqur (Jurnal Pena Indonesia, 2017)
Lack of school facilities, unavailability of literary laboratory, and the lack of media in teaching literature in the weakening interest in the study of literature, shortcuts taken by learners is looking for another facility (online media) to address the issues of literary study. Data search (literature) in online media is not without problems, copy and paste process dulls creativity of learners. In fact, the study of literature in schools can deliver the products literature (poetry, short stories, folklore, etc.), which can simultaneously create new writers. The development of creative industries in the fields of art, including the works of literature, to be able to force teachers and students to race in making literary works can be recorded and enjoyed by the public school